ECONOMIC EFFECTS OF THE APPLIANCE OF NEW TYPES OF MACHINES AND TOOLS FOR THE ARRANGEMENT OF SOILS IN SUNFLOWER PRODUCTION - Sasa Todorović; Zorica Vasiljević; Nikola Popović (Ekonomika Poljoprivrede (1979), 2010)
The need of preservation and rational use of natural resources such is land requires the elimination of the usual practice of production and application of new technologies and new types of machines and tools. However, massive acceptation and successful application of new technologies and new types of machines and tools in practice requires certificates of manifestation the positive technical, technological and economic effects obtained through appropriate research.